Immobilisation dose rates for Weddell seals during expedition PS146 (FIL2025) - Bornemann, Horst; Middleton, Leo; Schröder, Henning; Wege, Mia (PANGAEA, 2025)
Weddell seals (Leptonychotes weddellii) were immobilised during expedition PS146 (FIL2025) for the purpose of deployments with Conductivity, Temperature, Depth, Satellite Relay Data Loggers (CTD SRDL) and SCOUT CTD 370 FastLoc GPS satellite tags (SCOUT CTD). The CTD SRDL and SCOUT CTD tag deployments (n=13) were located at around the Filchner-Outflow-System (FOS) of the Filchner Trough, southern Weddell Sea. The seals were captured along the ships' tracks during ahead flights of the board helicopter and immobilised on fast (bay) and pack ice and captured along tidal cracks within and on ice flows and immobilised and instrumented with with Argos-linked (CLS, Toulouse, France) CTD SRDL (Sea Mammal Research Unit, UK) and SCOUT CTD tags (Wildlife Computers, US) to investigate their ranging and foraging behaviour in the context of oceanographic features.
Keywords: Immobilisation; Leptonychotes weddellii; Weddell seal